Low-dose total skin electron beam therapy in erythrodermic mycosis fungoides and Sézary syndrome: results from the prospective S-MISR study - Elsayad, Khaled; Kandler, Christian; Siats, Jan Jakob; Pepper, Niklas; Danzer, Moritz Fabian; Dobos, Gabor; Livingstone, Elisabeth; Melchers, Susanne; Kleemann, Johannes; Hyun, Julia; Pföhler, Claudia; von den Driesch, Peter; et al. (Journal der Deutschen Dermatologischen Gesellschaft, 2025)
Background Erythrodermic mycosis fungoides (eMF) and Sézary syndrome (SS) often show delayed and non-durable clinical responses to systemic therapies. Patients and Methods A total of 35 patients with eMF or SS were treated with total skin electron beam therapy (TSEBT). Response rates, patient-reported outcomes, survival data, median time to next treatment (TTNT), and progression-free survival (PFS) were evaluated. Results The analysis included 21 patients with SS and 14 with eMF. The median radiation dose was 12 Gy. At 3 months post-TSEBT, the overall response rate was 89%. A total of 25 patients (71%) required subsequent systemic therapy. The median TTNT was 20 months, and the median PFS was 14 months. Patients reported marked reductions in pruritus, decreased skin disease burden, and improved health-related quality of life scores. Notably, both TTNT and PFS were longer in patients who received subsequent therapy compared to those who did not. Grade ≥3 radiation-related toxicity was observed in 6% of patients. In the translational arm of the study, several potential peripheral blood biomarkers were identified. Conclusions Low-dose TSEBT is an effective treatment option for patients with eMF and SS, facilitating subsequent therapies and enabling long-term disease control. The treatment is associated with significant quality-of-life improvements and low toxicity.